The Literature Review in Grounded Theory - Tom Andrews (Grounded Theory Review: An International Journal)
The paper by McCallin (2003) is a useful contribution to the debate surrounding the role of the literature in Grounded Theory (GT). For the purpose of this paper and with reference to McCallin (2003) the issue will be discussed in relation to the purpose of a review within GT. It will be argued that the misunderstanding about the function of the literature within a GT study arises partly as a result of the confusion caused by the continual rewriting of the method. Further it will be argued that a preliminary reading of the literature is entirely consistent with the principals of GT. Finally some practical suggestions will be made as to how the issue could be dealt with in a way that is unproblematic for GT.